2003
DOI: 10.1042/bj20030830
|View full text |Cite
|
Sign up to set email alerts
|

Secretory phospholipases A2 induce neurite outgrowth in PC12 cells

Abstract: sPLA(2)s (secretory phospholipases A(2)) belong to a broad and structurally diverse family of enzymes that hydrolyse the sn -2 ester bond of glycerophospholipids. We previously showed that a secreted fungal 15 kDa protein, named p15, as well as its orthologue from Streptomyces coelicolor (named Scp15) induce neurite outgrowth in PC12 cells at nanomolar concentrations. We report here that both p15 and Scp15 are members of a newly identified group of fungal/bacterial sPLA(2)s. The phospholipid-hydrolysing activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 35 publications
1
51
1
Order By: Relevance
“…7). Although some AA metabolites have been reported to exert neuronal functions (40), the observation that cyclooxygenase and lipoxygenase inhibitors do not prevent neurite outgrowth of PC12 cells (41) argues against the contribution of AA metabolites to this event. Third, TLC and ESI/MS analyses demonstrated that sPLA 2 -X produces LPC with C16:0 and 18:0 in PC12 cells (Fig.…”
Section: Spla 2 -X Is Expressed In Peripheral Neuronal Fibers In Var-mentioning
confidence: 89%
“…7). Although some AA metabolites have been reported to exert neuronal functions (40), the observation that cyclooxygenase and lipoxygenase inhibitors do not prevent neurite outgrowth of PC12 cells (41) argues against the contribution of AA metabolites to this event. Third, TLC and ESI/MS analyses demonstrated that sPLA 2 -X produces LPC with C16:0 and 18:0 in PC12 cells (Fig.…”
Section: Spla 2 -X Is Expressed In Peripheral Neuronal Fibers In Var-mentioning
confidence: 89%
“…Such a "neuritogenic" property has been already reported for sPLA2s of groups IA and IB from cobra venom (Makarova et al, 2006;Osipov et al, 2010), IIA from viper venom (Makarova et al, 2006), III from bee venom (Nakashima et al, 2003) and from human neuronal cells (Masuda et al, 2008), V from mouse (Nakashima et al, 2003), X from mouse (Nakashima et al, 2003) and human (Ikeno et al, 2005;Masuda et al, 2005), as well as XIII from bacteria and fungi (Nakashima et al, 2003). According to the early report (Hanada et al, 1996), fungal PLA2 p15 promotes only NGF-induced neuritogenesis but itself alone fails to induce neurite outgrowth in PC12; however, under some conditions p15 can displays neuritogenic properties (Wakatsuki et al, 1999).…”
Section: Pla2 and Neurite Outgrowth In Pc12 Cellsmentioning
confidence: 96%
“…So, sPLA2 from bee venom being the most active among studied sPLA2s induces neurite outgrowth at concentration as low as 0.1 nM. sPLA2 of group XIII is effective starting from 1 nM (Nakashima et al, 2003), and snake venom sPLA2s of groups IA, IB, and IIA are effective at concentrations of 1-10 M (Makarova et al, 2006;Osipov et al, 2010). Not all of sPLA2s can induce neuritogenesis:…”
Section: Pla2 and Neurite Outgrowth In Pc12 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the virulence of many microbes, including viruses (Canaan et al 2004), fungi (Nakashima et al 2003), and bacteria (Phillips et al 2003), involves secretion of toxic microbial PLA2s; however, the details of PLA2-mediated microbe-host interactions can be complex. At least some toxic PLA2s are thought to exert their influence via receptor-mediated events (Cupillard et al 1999) and via direct cell damage.…”
Section: Discussionmentioning
confidence: 99%